A5 7 Big Mantis - Taylor, Josh; Edward Greathead; Jaspreet Rai (Physics Special Topics, 2024)
In this short study we investigated the difference in energy imparted by the striking arm of a regularly sized Peacock Mantis shrimp and a hypothetical version of this shrimp that was scaled to the size of a human. The mechanical energy involved in producing a blow from the striking arm was found to be 9.3 mJ for the smaller crustacean and 13.1 kJ for the larger one.